Factores Que Afectan El Desarrollo Embrionario Gonadal Del Tracto Reproductivo En Hembras Bovinas Freemartin Y Sus Diagnósticos- Revisión (2022)
Freemartin syndrome is the pathology that affects cattle in a large percentage, and may occur in other species, to a lesser extent, the literature groups extensive research works that have gone through time compiling history of factors related to poor gonadal development, Anatomical alterations present in this syndrome revealing the effects on internal genitalia such as gonadal hypoplasia, incorrect development of Müllerian duct derivatives and the presence of Wolff derivatives (Ayala et al, 2000). In the present work the general objective is to carry out the compilation of factors that flourish the embryonic development of the gonads of the reproductive tract in females born from heterosexual twin birth and their diagnoses. At the end of the data collection, it was possible to conclude that the causes of freemartin are vascular anastomosis resulting in XX, XY chimeras accompanied by the crossing of male hormones that caused great economic losses, the most accessible and rapid diagnostic method is cytogenetic analysis by culture of lymphocytes accompanied by a previous clinical examination.